2014
DOI: 10.1002/14651858.cd008785.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions based on the Theory of Mind cognitive model for autism spectrum disorder (ASD)

Abstract: Interventions based on the Theory of Mind cognitive model for autism spectrum disorder (ASD). Cochrane database of systematic reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 133 publications
4
104
0
4
Order By: Relevance
“…Likewise, it will be important for anyone implementing interventions such as those described here to include instruction in natural settings with structured opportunities to promote the student's ability to understand other people's points of view. Adopting a core deficit model to explain diminished competencies of ToM may require a longitudinal study that will examine ToM as a result of a chain of precursor skills (Fletcher-Watson et al, 2014). Unlike most ToM training programs that last a few weeks to a few months, we suggest a longitudinal training program that would allow for within-subject comparisons while cognitive, language, and social development take their natural course.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, it will be important for anyone implementing interventions such as those described here to include instruction in natural settings with structured opportunities to promote the student's ability to understand other people's points of view. Adopting a core deficit model to explain diminished competencies of ToM may require a longitudinal study that will examine ToM as a result of a chain of precursor skills (Fletcher-Watson et al, 2014). Unlike most ToM training programs that last a few weeks to a few months, we suggest a longitudinal training program that would allow for within-subject comparisons while cognitive, language, and social development take their natural course.…”
Section: Discussionmentioning
confidence: 99%
“…This training is related to Baron-Cohen's concept of EDD and its relatedness to SAM and ToM. It follows the perspective of a core deficit model (Fletcher-Watson et al, 2014). Intervention C, in contrast, was based on training students on the idea that people may have true and false beliefs.…”
Section: Procedures and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of 22 randomized controlled ToM interventions in ASD samples (N ¼ 695) showed little evidence of their efficacy; the only positive effect was improvement in emotion recognition in those of average intellectual ability [55]. A crucial, yet understudied, aspect of interventions is how children with ASD might differ from typically developing controls in their understanding of pedagogical communication [56 & ].…”
Section: Interventionsmentioning
confidence: 99%